Building vulnerabilities to fires at the wildland urban interface - Laranjeira, J. (2014)
Fires on the Wildland Urban Interface (WUI) have caused significant loss of life and colossal property and natural environment damages in numerous countries around the world. The solutions to mitigate this fire problem are complex, as it results from the fuel source changes from vegetation to structural materials in a fireprone environment and it involves the interaction of several factors that act synergistically to increase the frequency of fires with severe potential destruction. In order to understand how and why buildings are damaged and destroyed under wildland fire attack, several surveys following historical large scale fire events, which resulted in significant building damages and/or losses, have been conducted worldwide. This paper aims to review and analyse the main characteristics of buildings and other structures that contributed to their vulnerability during fires at the WUI, based on the analysis of several post fire studies developed in Australia, United States of America and Mediterranean Europe (particularly Portugal, Spain, Greece). The different building traditions between the selected countries are discussed, as long as they affect building vulnerability to fires.